Unconventional splicing of wheat TabZIP60 confers heat tolerance in transgenic Arabidopsis. (September 2018) - Geng, Xiaoli; Zang, Xinshan; Li, Haoran; Liu, Zhenshan; Zhao, Aiju; Liu, Jian; Peng, Huiru; Yao, Yingyin; Hu, Zhaorong; Ni, Zhongfu; Sun, Qixin; Xin, Mingming
Highlights: TabZIP60 splicing occurs in wheat under heat stress condition. Over expression of TabZIP60s in Arabidopsis enhances heat stress tolerance. We identified the downstream targets of TabZIP60s using ChIP-qPCR strategy, which contribute to great biological importance to heat tolerance. The 26S proteasome pathway post-translationally regulates TabZIP60s levels during heat stress responses. Abstract: Conditions that disrupt protein folding, such as heat stress, can overwhelm the capacity of cells to fold proteins, thus causing endoplasmic reticulum (ER) stress. In Arabidopsis thaliana and other plants, inositol-requiring enzyme-1 mediated unconventional splicing of bZIP60 plays a crucial role in the heat and ER stress responses. However, little is known about this pathway in wheat ( Triticum aestivum ), especially its importance in heat tolerance. Here, we found that heat stress induced upregulation and unconventional splicing of TabZIP60 occurred in wheat seedlings. Constitutive expression of the spliced form of TabZIP60 ( TabZIP60s ) enhanced heat tolerance in Arabidopsis, but overexpression of the unspliced form ( TabZIP60u ) did not. RNA-sequencing analysis revealed ER stress related genes involved in heat responses in TabZIP60s- overexpression transgenic Arabidopsis. Chromatin immunoprecipitation-qPCR showed that TabZIP60s directly binds to 17 target genes including AtbZIP60 . Also, the 26S proteasome pathway post-translationally regulates TabZIP60s levels during heat stress responses. Our findings suggest that unconventional splicing of TabZIP60 could contribute to heat tolerance in transgenic plants by modulating the expression of ER stress-related genes.